The diagnostic algorithm in pre-invasive cervical lesions - Mihai-George Loghin; Oana Denisa Balalau; Nicolae Bacalbasa; Adriana Vasilache; Octavian Gabriel Olaru; Andrei Vasilache; Anca Daniela Stanescu (Journal of Mind and Medical Sciences)
The screening for pre-invasive cervical lesions has significantly decreased the incidence of cervical neoplasm. It is recommended to be performed starting with the age of 21 with a frequency of 3-5 years and it consists of pap smear testing and HPV genotyping, and, if required, it can be continued with colposcopy or biopsy followed by pathological assessment. The importance of the early diagnosis of pre-invasive cervical lesions has led to several studies on this topic. The paper analyzed the modern literature published on the PubMed and Scopus databases. Reference studies have found that most intraepithelial lesions are caused by the presence of HPV. Other commonly associated factors are immunosuppression, multiparity and other viral infections. HPV infection can be prevented by vaccination. It is recommended for people between 11 and 26 years old and also over 27 years old if they associate risk factors. A meta-analysis performed on patients diagnosed with CIN2 revealed a lower recurrence rate in vaccinated women than in unvaccinated women. Other studies have shown the transient nature of HPV infection and spontaneous regression of pre-invasive lesions. The early diagnosis of pre-invasive lesions is necessary for the initiation of therapeutic and follow-up behavior as soon as possible, with the aim of reducing the incidence of cervical cancer. This is possible and easy to access through national health programs.